A new species of Isthmura (Caudata: Plethodontidae) from the montane cloud forest of central Veracruz, Mexico - Sandoval-Comte, Adriana; Pineda, Eduardo; Rovito, Sean M.; Luría-Manzano, Ricardo (Zootaxa, 2017)
We describe a new plethodontid salamander species of the genus Isthmura, known only from one locality in the mountainous region of central Veracruz, Mexico. Like its congeners, Isthmura corrugata sp. nov. has a large and robust body, but it is easily distinguished from the other species in the genus by the absence of any spot or mark on the dorsum (except by dull reddish brown coloration on eyelids) and by extremely well-marked costal grooves separated by very pronounced costal folds. Based on an mtDNA phylogeny, the new species is most closely related to the geographically distant I. boneti and I. maxima but occurs very near I. naucampatepetl and I. gigantea on the eastern slope of Cofre de Perote, Veracruz. The region where I. corrugata occurs contains a high number of plethodontid salamander species and is threatened by human activity.